Dual Responsive Disposable Electrode for the Enumeration of Escherichia coli in Whole Blood. Issue 10 (16th July 2020) - Panhwar, Sallahuddin; Ilhan, Hasan; Hassan, Syeda Sara; Zengin, Adem; Boyacı, Ismail Hakkı; Tamer, Ugur
Abstract: In this report, we have designed a dual responsive disposable electrode for the enumeration of Escherichia coli K12 (E. coli K12) . The immunomagnetic separation strategy provided easily bacterial detection in the whole blood. Metal‐organic frameworks magnetic (MOFs) modified, and citrate capped gold nanoparticles were used as capture probe and spectro‐electrochemical labels, respectively. The cyclic voltammetry (CV) was employed to quantify E. coli with a ranging from 10 1 to 10 7 cfu/mL with a LOD of 1 cfu/mL. The Surface enhanced Raman spectroscopy (SERS) measurements were also performed with using disposable electrode. Abstract :